2008
DOI: 10.1007/s00421-008-0908-2
|View full text |Cite
|
Sign up to set email alerts
|

The stress of chess players as a model to study the effects of psychological stimuli on physiological responses: an example of substrate oxidation and heart rate variability in man

Abstract: We have studied the physiological consequences of the tension caused by playing chess in 20 male chess players, by following heart rate, heart rate variability, and respiratory variables. We observed significant increase in the heart rate (75-86 beats/min), in the ratio low frequency (LF)/high frequency (HF) of heart rate variability (1.3-3.0) and also a decrease in mean heart rate variability with no changes in HF throughout the game. These results suggest a stimulation of the sympathetic nervous system with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 36 publications
0
34
2
Order By: Relevance
“…Closer to real competition, during a chess game, a legitimate psychological stress environment, a pair of studies assessing HRV have been conducted. In the former, Schwarz et al (2003) showed an association between increasing helplessness/hopelessness ratio and reduced vagal activity; whereas in the latter Troubat et al (2009) suggested a stimulation of the sympathetic branch with no changes in parasympathetic activity during chess game. Only one study, to the best of our knowledge, has previously used HRV to explore cardiac autonomic regulation in the moments prior to competition; finding a shift towards sympathetic predominance as a result of decreased parasympathetic activity, and suggesting HRV as a valid, practical and non-invasive way to assess changes in sympathetic-parasympathetic balance in the presence of competitive stress (Cervantes Blásquez et al 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Closer to real competition, during a chess game, a legitimate psychological stress environment, a pair of studies assessing HRV have been conducted. In the former, Schwarz et al (2003) showed an association between increasing helplessness/hopelessness ratio and reduced vagal activity; whereas in the latter Troubat et al (2009) suggested a stimulation of the sympathetic branch with no changes in parasympathetic activity during chess game. Only one study, to the best of our knowledge, has previously used HRV to explore cardiac autonomic regulation in the moments prior to competition; finding a shift towards sympathetic predominance as a result of decreased parasympathetic activity, and suggesting HRV as a valid, practical and non-invasive way to assess changes in sympathetic-parasympathetic balance in the presence of competitive stress (Cervantes Blásquez et al 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Only in highly trained endurance athletes may blood oxygen saturation fall during heavy exercise [2]. Troubat [14] observed in his study a constant ventilation rate, so that a limitation of O 2 during mental activity was excluded.…”
Section: Discussionmentioning
confidence: 97%
“…A limitation of the study of Troubat [14] remains because of the relative short time of the game (on the average 45 minutes for each player). In blitz-chess tournaments for example, the players have only 5 minutes for the complete game so that 10times as many conflict situations must be solved per time unit.…”
Section: Energy For Chess Performancementioning
confidence: 99%
See 2 more Smart Citations